Novel methods to diagnose leptomeningeal metastases in breast cancer. Issue 4 (10th November 2018) - Angus, Lindsay; Martens, John W M; van den Bent, Martin J; Sillevis Smitt, Peter A E; Sleijfer, Stefan; Jager, Agnes
Abstract: Leptomeningeal metastases (LM) in breast cancer patients are rare but often accompanied by devastating neurological symptoms and carry a very poor prognosis, even if treated. To date, two diagnostic methods are clinically used to diagnose LM: gadolinium MRI of the brain and/or spinal cord and cytological examination of cerebrospinal fluid (CSF). Both techniques are, however, hampered by limited sensitivities, often leading to a long diagnostic process requiring repeated lumbar punctures and MRI examinations. To improve the detection rate of LM, numerous studies have assessed new techniques. In this review, we present the current workup to diagnose LM, set out an overview of novel techniques to diagnose LM, and give recommendations for future research.